Assessment of the nutritional status of hospitalized children: why and how to assess? |Evaluation de l’état nutritionnel de l’enfant hospitalisé : pourquoi et comment évaluer ?] - Kaïs S. BOUK’HIL; Ourida GACEM (Nutrition & Santé)
Hospital pediatric malnutrition remains largely underdiagnosed, even though it affects up to 30% of hospitalized children in high-income countries. It directly impacts prognosis: increased infectious complications, prolonged hospital stays, delayed reco-very, impaired neurocognitive development, and excess mortality. A new definition, pro-posed by the American Society for Parenteral and Enteral Nutrition (ASPEN), and endorsed by the American Academy of Pediatrics, recommends an etiological approach that considers the pathological context, chronicity, inflammation, and anthropometric deterioration. Two main types are distinguished: disease-related and non-disease-rela-ted malnutrition. Nutritional assessment must be systematic from the time of admis-sion. It combines medical record analysis, targeted interviews (intake, digestive symp-toms, social factors), anthropometric measurements (weight, height, circumferences), and nutrition-focused physical examination (muscle wasting, skin and mucosal findings, etc.). Nutritional indices are essential but must be interpreted cautiously. Pediatric scre-ening tools (STRONGkids, PYMS, STAMP) have been developed but still lack large-scale validation. Early screening for malnutrition is a clinical priority, as it allows for timely nutritional intervention, preventing long-term sequelae. Team training in proper measu-rement techniques, indicator interpretation, and thoughtful use of screening tools is essential to fully integrate nutrition into the overall care of hospitalized children. [La malnutrition pédiatrique hospitalière reste largement sous-diagnostiquée, bien qu’elle touche jusqu’à 30 % des enfants hospitalisés dans les pays à revenu élevé. Elle impacte directement le pronostic : complications infectieuses accrues, allongement de la durée d’hospitalisation, retard de récupération, altération du développement neurocognitif et surmortalité. Une nouvelle définition, proposée par l’American Society for Parenteral and Enteral Nutrition (ASPEN) et validée par l’American Academy of Pediatrics (AAP), recommande une approche étiologique, tenant compte du contexte pathologique, de la chronicité, de l’inflammation et de la dégradation anthropomé-trique. Deux formes principales sont distinguées : malnutrition liée ou non liée à une pathologie. L’évaluation nutritionnelle doit être systématique, dès l’admission. Elle combine une analyse du dossier médical, un entretien ciblé (apports, symptômes digestifs, facteurs sociaux), des mesures anthropométriques (poids, taille, périmètres) et un examen clinique nutritionnel (fonte musculaire, atteinte cutanéo-muqueuse, etc.). Les indices nutritionnels sont essentiels mais doivent être interprétés avec précaution. Des outils de dépistage pédiatriques (STRONGkids, PYMS, STAMP) ont été développés, mais restent à valider à grande échelle. Le dépistage précoce de la malnutrition est une priorité clinique, car il permet une intervention nutritionnelle rapide, évitant des séquel-les à long terme. Une formation des équipes aux bonnes pratiques de mesure, à l’inter-prétation des indicateurs et à l’utilisation raisonnée des outils est indispensable pour intégrer pleinement la nutrition dans la prise en charge globale de l’enfant hospitalisé.]